Cultural citizenship : cosmopolitanism, consumerism, and television in a neoliberal age - Miller, Toby, 1958- (Temple University Press, 2007)
What does it mean to be a "citizen" today, in an age of unbridled consumerism, terrorism, militarism, and multinationalism? In this passionate and dazzling book, Toby Miller dares to answer this question with the depth of thought it deserves. Fast-moving and far-ranging, Cultural Citizenship blends fact, theory, observation, and speculation in a way that continually startles and engages the reader. Although he is unabashedly liberal in his politics, Miller is anything but narrow minded. He looks at media coverage of September 11th and the Iraq invasion as well as "infotainment"--Such as Food and Weather channels-to see how U.S. TV is serving its citizens as part of "the global commodity chain." Repeatedly revealing the crushing grip of the invisible hand of television, Miller shows us what we have given up in our drive to acquire and to "belong." For far too long, "cultural citizenship" has been a concept invoked without content. With the publication of this book, it has at last been given flesh and substance